2003
DOI: 10.1073/pnas.0637114100
|View full text |Cite
|
Sign up to set email alerts
|

Small ubiquitin-like modifier conjugation regulates nuclear export of TEL, a putative tumor suppressor

Abstract: Posttranslational modification by small ubiquitin-like modifier (SUMO) conjugation regulates the subnuclear localization of several proteins; however, SUMO modification has not been directly linked to nuclear export. The ETS (E-Twenty-Six) family member TEL (ETV6) is a transcriptional repressor that can inhibit Rasdependent colony growth in soft agar and induce cellular aggregation of Ras-transformed cells. TEL is frequently disrupted by chromosomal translocations such as the t(12;21), which is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 63 publications
(80 reference statements)
6
103
0
2
Order By: Relevance
“…The C-terminal ETV6 mutations were either inframe or resulted in truncation of the ETS domain by out-of-frame mutation. In concordance with earlier studies (Waga et al, 2003;Wood et al, 2003), the truncated ETV6 proteins were impaired in repressing transcription in a ETV6-specific luciferase assay. Moreover, coexpression of the mutants with an intact homodimerization domain (#2236, 3102, 2649 and N) completely abolished the transcription repression by wt ETV6.…”
Section: Discussionsupporting
confidence: 77%
“…The C-terminal ETV6 mutations were either inframe or resulted in truncation of the ETS domain by out-of-frame mutation. In concordance with earlier studies (Waga et al, 2003;Wood et al, 2003), the truncated ETV6 proteins were impaired in repressing transcription in a ETV6-specific luciferase assay. Moreover, coexpression of the mutants with an intact homodimerization domain (#2236, 3102, 2649 and N) completely abolished the transcription repression by wt ETV6.…”
Section: Discussionsupporting
confidence: 77%
“…Work in Dictyostelium on the MAP kinase MEK-1 revealed that SUMOylation is required for MEK1's translocation from the nucleus to the cytosol (Galy et al, 2002). A similar mechanism was proposed recently for the transcriptional repressor TEL (Wood et al, 2003). The localization of a SUMO-ligase at the nuclear pore now strengthens the idea that SUMOylation is coupled to nuclear transport processes.…”
Section: E3-like Ligases and Isopeptidases As Regulators In The Sumo supporting
confidence: 55%
“…For example, SUMO has been implicated in promoting the nuclear retention of the Elk-1 transcription factor (Salinas et al 2004), adenoviral E1B-55K protein (Kindsmuller et al 2007), and CtBP1 corepressor (Lin et al 2003b). In terms of SUMO promoting nuclear export, as our data suggest for Med, examples include the TEL repressor protein (Wood et al 2003), MEK1 kinase (Sobko et al 2002), ribosome biogenesis factors (Panse et al 2006), and p53 transcription factor (Carter et al 2007).…”
Section: Sumoylation Promotes Med Nuclear Exportmentioning
confidence: 80%